MANAGEMENT OF RAPIDLY PROGRESSIVE PRECOCIOUS PUBERTY IN A PATIENT WITH MOSAIC TURNER SYNDROME - GÜRAN, TÜLAY (EDITURA ACAD ROMANE, 2021)
Context. Rapidly progressive precocious puberty (RPPP) is a rare condition in Turner syndrome (TS), with no consensus on treatment and follow-up. Only 12 cases have been reported so far. Objective. We aimed to evaluate the effects of the GnRH analog (GnRHa) on growth and anti-mullerian hormone (AMH) levels in TS and RPPP. Design. The clinical and laboratory data was recorded at baseline and after treatment. Subjects and methods. An 8.1-year old girl with a karyotype of 45, X/46, XX presented with breast development at Tanner stage-2. Breast development advanced to Tanner stage-3 at the age of 8.7 years. Growth velocity (GV) was 8 cm/year. Bone age was 11 years with a predicted adult height of 152 cm. Luteinizing hormone (LH) was 1.69mIU/mL and estradiol was 33pg/mL, confirming the central puberty. AMH level was 6.33ng/mL. The sizes of ovaries and uterus were compatible with the pubertal stage, with an endometrial thickness of 5 mm. GnRHa was started for RPPP. Results. After three months, GV declined to 0 cm/3 months and AMH level to 50% of the baseline. Growth hormone (GH) treatment was started for insufficient growth. GV improved with GH treatment, as well as a far more decreased AMH level. Conclusion. GV usually declines before puberty in patients with TS, even if the mid-parental height is tall. RPPP should be considered if GV is increased. Excessive suppression of growth may be prevented with GH treatment. GnRHa treatment also plays a role in reducing AMH levels in patients with TS.
Keywords: GnRH analog; Rapidly progressive precocious puberty; Turner syndrome; ANTI-MULLERIAN HORMONE; SERUM-LEVELS; GIRLS